Muhammad Al-Ghazali's Da'wah Thoughts In The Book Of Fi Mawkib Al-Da'wah And Ma'a Allah; Dirasat Fi Al-Da’wah Wa Al-Du’at - Choirin, Muhammad; Lubis, Adlan Fauzi (Universitas Islam Negeri (UIN) Mataram, 2023)
This article examines Shaikh Muhammad al-Ghazali's preaching thoughts regarding the concepts and principles of da'wah. Apart from exploring the character of Shaikh Muhammad al-Ghazali and his work in the field of Islamic da'wah, this article analyzes several issues related to the concept and principles of da'wah. In both books, he discusses in detail the meaning of preaching, the theme of preaching, the approach to preaching and the media of preaching. This research found that Muhammad al-Ghazali was an accomplished world-class preacher. His various theories and ideas related to da'wah are very brilliant in the context of advancing contemporary da'wah, both related to the provisions of preachers, the approach and also the media for implementing da'wah as well as the problems of da'wah and solutions that can be used by preachers in the future